Perkembangan Keuangan Islam di Eropa - Henny Saptatia D. Nugrahani; Agung Permadi; Yulinar Amalia Masfufah (Jurnal ICMES, 2020)
This study analyzes the implications of cooperation between United Kingdom (UK) and Bahrain, especially the international financial institution Al-Baraka, in developing Islamic banking. The UK is a non-Middle Eastern country that has developed Islamic finance since the entry of the Al-Baraka international financial institution from Bahrain in 1982. At present, the UK is the centre of Islamic banking in Europe and plays an essential role in the Islamic banking sector. This study analyzes the British policy in opening up the Islamic Bank of Britain (IBB) and the cooperation process with the Al-Baraka financial institution from an international relations perspective. The theory used in this qualitative research is the Regional Security Complex. The concept of amity and enmity in the Regional Security Complex is used to see how this collaboration could be established. The findings of this study are that the UK is a potential market in the development of Islamic banking in Europe and the cooperation that existed between Britain and Bahrain in the development of Islamic banking occured in the dynamics of amity and enmity. Between the two parties, there was not only friendly relations but also British suspicion of Al-Baraka financial institution which has the potential to become a dominant financial institution and displace conventional financial institutions.